THEORETICAL REFLECTION ON THE CONCEPT OF PERCEIVED QUALITY FROM AN ARCHITECTURAL PERSPECTIVE - Abdeldjalil Hamdaoui; Mohamed Cherif Adad; Ismahane Haridi; Ahmed Mounir Ansar (International Journal of Innovative Technologies in Social Science, 2024)
This paper is dedicated to exploring the subjective dimension of architectural quality, emphasizing the importance of understanding how individuals perceive architectural structures and spaces. To fully grasp this perception, it is essential to examine the multifaceted elements that capture the observer’s attention, including the style, scale, form, color palette, and spatial organization of the building. Each of these factors contributes to the way a structure is experienced and interpreted, either in isolation or as part of an integrated whole. The combination of these elements can provoke a wide array of responses, ranging from aesthetic appreciation to emotional reaction, and thus, architectural design becomes a dynamic process that engages various facets of human experience. This paper aims to contribute to the body of knowledge surrounding architectural quality. The insights gained through this exploration hold the potential to inform and inspire design practices that foster greater aesthetic, functional, and emotional resonance with the individuals who engage with these spaces. Given the diverse and individualized nature of these responses, it is crucial to consider perception as a complex phenomenon in itself, one that not only encompasses sensory input but also emotional, cognitive, social, and cultural factors that influence how a building is perceived. Understanding this phenomenon allows architects and designers to identify the specific qualities that may enhance the effectiveness of their designs.